Sub-optimal nonlinear predictive and adaptive control based on the parametric Volterra model - Haber, Robert; Bars, Ruth; Lengyel, Orsolya (Zielona Góra: Uniwersytet Zielonogórski)
Predictive control algorithms have been worked out mainly to control linear plants. There is a great demand to apply different control ideas to nonlinear systems. Using predictive control algorithms for nonlinear systems is a promising technique. Extended horizon one-step-ahead and long-range optimal predictive control algorithms are given here for the parametric Volterra model (which includes also the generalized Hammerstein model).
Keywords: predictive control; nonlinear control; optimal control; nonlinear systems; adaptive control